Effects on visual search of lesions of the superior colliculus in infant or adult rats. - Heywood, C; Cowey, A (1987)
The superior colliculus was removed from rats at either one or five days of age or in maturity. Four months later they were tested on two versions of a visual search task. Experiment 1 required animals to retrieve food pellets concealed in a depression in the top of identical narrow pillars arranged in an arena. Rats with lesions of the superior colliculus, regardless of the age at operation, showed a large number of 'return' errors compared with sham-operated controls. Return errors were defined as occasions on which the animal returned to pillars that had previously been visited on that trial, before every pillar had been visited at least once. Experiment 2 compared the ability of infant- and adult-operated animals to detect and locate a single, baited white pillar in an array of black ones. There were no group differences in response latencies to targets presented in the rostral visual field (within 40 degrees of the midline). However, animals operated on in adulthood or at 5 days of age were slower than both sham-operated animals and animals operated on at one day of age in their responses to more peripheral targets. The latter two groups were indistinguishable.